Analisis Pelanggaran Ketenagakerjaan (Studi Kasus Pt. Indonesia Bakery Family) - Ahmad Fadhil Haida; Rizky Sri Hapsari; Rr. Luh Sekar Nur Sukmawati; Roderick Natanael (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
: This article examines violations of labor regulations from the perspective of related laws and regulations as well as the potential legal impacts of these violations. Analysis of several examples of employment regulations that often appear in the world of work was carried out by referring to Law Number 13 of 2003 concerning Employment and its derivative regulations. Various violations were detected through case studies, including non-procedural termination of employment, mishandling of working hours, providing wages below standard, and not providing occupational safety and health protection. The legal consequences of these violations are examined, along with the responsibilities of the parties involved. This includes administrative and civil sanctions for employers who violate labor laws. The importance of complying with labor laws for the creation of fair and positive employment relationships is emphasized in the conclusion, as is the importance of employers and employees being aware of these laws to avoid violations in the future.